SEJARAH PERKEMBANGAN LEMBAGA PENDIDIKAN ISLAM DI INDONESIA - M. Herlambang; Muqowim Muqowim; Rofik Rofik (Tarbiyatuna Kajian Pendidikan Islam, 2024)
Islamic education in Indonesia has a long and complex history, with developments that have occurred since the beginning of Islam's arrival in the archipelago. This article discusses how Islamic educational institutions in Indonesia have developed over time, and how they have adapted to social and cultural changes in society. In this article, we will discuss the development of Islamic educational institutions in Indonesia, starting from the early days of informal Islamic education to the present day with Islamic education integrated with the national education system.